EVALUATING BRAND IMAGE AND CONSUMER PRODUCT KNOWLEDGE OF APPLE SMARTPHONE IN MANADO - Sanggor, Eukaristia M; Pangemanan, Sifrid S.; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract : Telecommunication device help people to communicate with other people at a distance. Telecommunication industry also make the high growth rate of this industry over the past few decades and the significant contribution of the industry to the economies of the nations. The aim for this study is to evaluating brand image and consumer product knowledge of Apple smartphone in Manado. This research has identified 2 variables of brand image and product knowledge Brand image is the perception of brand that created in memory of consumer due to brand involvement. Product knowledge as a perception consumers have towards certain products, including previous experience of using the product. The population of this research is all the customers that use Apple smartphone (iPhone) in Manado. The sample of this research using Non probability sampling with 100 people have experience using Apple smartphone in Manado. The result from this research Apple smartphone is needs a periodic assessment about the performance of brand image and product knowledge so the program that established always meets the customer’s satisfaction in needs or expectation. Keywords : brand image, product knowledge, importance and performance analysis